2016
DOI: 10.1007/s12012-016-9381-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrary microRNA Expression Pattern Between Fetal and Adult Cardiac Remodeling: Therapeutic Value for Heart Failure

Abstract: microRNAs (miRNAs) belong to a class of non-coding RNAs that regulate post-transcriptional gene expression during development and disease. Growing evidence indicates abundant miRNA expression changes and their important role in cardiac hypertrophy and failure. However, the role of miRNAs in fetal cardiac remodeling is little known. Here, we investigated the altered expression of fifteen miRNAs in rat fetal cardiac remodeling compared with adult cardiac remodeling. Among fifteen tested miRNAs, eleven and five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…It was reported that miR-214-3p was differentially expressed in rat fetal and adult cardiomyocytes in response to the injection of isoproterenol, which supports that miR-214-3p is a potential marker of HF. 27 In the present study, however, the prevalence of CHF was not significantly different among the AC and AF patients. In addition, all 4 selected miRNAs showed no correlation with plasma BNP levels.…”
Section: Pathological Mirnas In Relation To Afcontrasting
confidence: 70%
“…It was reported that miR-214-3p was differentially expressed in rat fetal and adult cardiomyocytes in response to the injection of isoproterenol, which supports that miR-214-3p is a potential marker of HF. 27 In the present study, however, the prevalence of CHF was not significantly different among the AC and AF patients. In addition, all 4 selected miRNAs showed no correlation with plasma BNP levels.…”
Section: Pathological Mirnas In Relation To Afcontrasting
confidence: 70%
“…MiR-155-3p is down-regulated in heart of fetal and adult cardiac remodeling, an adaptive alteration that results an altered heart structure and function, when compared to control group. By contrast, miR-155-5p is up-regulated [ 37 ]. It has been shown that miR-155 level in proliferating cardiomyocyte progenitor cells is higher than differentiated cardiomyocyte progenitor [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In combination with other researchers 'statistics on sample size, we selected more than 60 healthy samples and more than 60 cases of heart failure. Exhaustion samples were analyzed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As shown in Figure 1, the aim of the present study was to identify circulating miRNAs in human plasma as biomarkers for the diagnosis of heart failure and its related diseases, to assess the appropriate biomarkers for identifying key characteristics of miRNAs, and to analyze their performance.…”
Section: Introductionmentioning
confidence: 99%